Escalation and Regulation of Emotional Arousal in Couples Predicts Relationship Satisfaction Concurrently and 25 Years Later - Weber, Danielle; Fischer, Melanie; Baucom, Donald H.; Baucom, Brian R. W.; Engl, Joachim; Thurmaier, Franz; Wojda, Alexandra K.; Hahlweg, Kurt (Family process, 2021)
Relationship distress and divorce are major risk factors for the development or exacerbation of psychopathology and psychosocial impairments. Given that heightened negative emotions within couples’ interactions may portend negative relationship outcomes, it is critical to understand how emotions unfold across a conversation and how partners may influence each other’s immediate emotional experiences. This study examined whether these regulatory dynamics within one interaction predicted relationship satisfaction concurrently and 25 years later. Vocally-encoded emotional arousal (f0) was measured during couples’ (N = 25 couples) conversations about a relationship issue. Across different analytical strategies, results demonstrate that one partner’s f0 dynamics had immediate and long-term associations with the other partner’s satisfaction. Partners were less satisfied if the other partner (a) expressed higher f0 overall and (b) escalated more in f0 across the conversation. Yet, partners were more satisfied when their f0 escalated across the conversation. Also, women specifically were more satisfied if their f0 remained elevated longer before regulating back to their emotional baseline. Thus, higher f0 was associated with higher satisfaction in the same partner, but associated with less satisfaction in the other partner—particularly when these emotions come from women. It may be that partners have to decide whether to prioritize expressing their emotions fully or limit expression in the service of their partner’s happiness. These findings challenge us to think of ways to address this “win-lose” scenario so that couples can balance both partners’ emotional needs and preserve relationship quality across the life span.
Online publiziert: 25. September 2020
Gesehen am 04.09.2025